Standardisation and quality evaluation of coconut based filled paneer - Suvarna Mohan (Department of Home Science, College of Horticulture, 2014)
The present study entitled “Development and quality evaluation of fruit based instant snack and pasta product” was carried out at Dept of Home Science, College of Agriculture, Vellayani, Trivandrum during the period 2011 to 2014. The objective of the study was to develop fruit based ready to eat instant snack and ready to cook pasta product by incorporating locally available fruits and also to assess the quality aspects such as nutritional, chemical, shelf stability and consumer acceptance and preference. Part .I. Development of instant snack The ingredients in instant snack product were jackfruit, papaya, banana, parboiled rice, wheat, horse gram, green gram and coconut. Each component had undergone various degrees of processing and optimization. Eight different combinations (C1, C2, C3, C4, C5, C6, C7 and C8) of the instant snack were worked out, from which the best combination C2 was selected based on the nutrient content and sensory evaluation by selected trained panel members. The ratio of the selected combination was 1: 1: 1: 2: 1: 2: 1: 1. The nutritional analysis revealed that instant snack had 349. 8 K Cal, 10.83 g protein, 66.96 g carbohydrates and 4.9 g fat per 100 g of the product. Organoleptic evaluation of the product emphasized that the flavor parameter was highly scored (5.8/6) and all the other parameters were also equally scored well above 5 out of 6. The highlight of the storage study conducted for 3 months showed that there was no significant difference in sensory parameters and chemical constituents and no microbial growth was observed. Consumer acceptance and preference study conducted among three different groups (children, adolescents and adults) showed that all the participants equally preferred the developed instant snack with mean scores ranging from 7.78 to 7.84 out of 9. The cost of the developed instant snack was Rs-170/- per Kg. Part .II. Development of pasta The second part of study, focused on the incorporation of fruits, jack fruit (Koozha) papaya (Pusa Dwarf), banana (Nendran) along with other ingredients ie green gram flour, wheat flour, and tapioca starch for the production of pasta. Different proportions of various ingredients such as wheat flour, green gram flour, tapioca starch, and fruit pulps were tried out for the pasta production. A total number of 19 proportions of pasta were tried out using banana pulp, papaya pulp, jack fruit pulp and mixed fruit pulp.Based on the Mass Flow Rate (MFR) best four proportions were selected from each fruit being banana pasta (P1B), papaya pasta (P2P), jackfruit pasta (P3J) and mixed fruit pasta (P4MF). The MFR values ranged from 0.52 to 2.72. The least MFR value was shown by P3J (0.52). P2P shown greater MFR value (2.72), followed by P4MF (2.11), and P1B (1.79). The ratios of selected proportions of pasta were 3: 5: 1: 1. Physical characteristics such as swelling index, water absorption index, cooking time, cooking loss, colour, and texture were analyzed and found significant difference in certain characters amongst the selected proportions of pasta. The sensory study indicated that the overall score was high for the P1B. The calorie content for P2P, P3J and P4MF pastas were 338.68, 368.65 and 368.65 respectively. Carbohydrates were found to be high in P1B (58.56) followed by P3J (56.91), P4MF (54.46). P2P (51.56) had the lowest carbohydrate content. In general, the nutrient content of P1B was relatively high. Even though a decreasing trend was observed for sensory scores of stored pasta, no significant difference was noticed. Analysis of chemical constituents of developed stored pasta also had no significant change. Fungal and yeast growth was observed only in the third month of storage for all the stored pasta samples. The consumer acceptance and preference study among children, adolescents and adults showed that the product pasta was highly preferred by adolescents followed by adults and children. The costs of the developed products ranged from Rs. 240/- per Kg to 265/- per Kg. Nevertheless, the well accepted ready to eat snacks and pasta products that were developed in the study can be scaled up for potential commercialization and marketing. Other underutilized fruits also can be similarly utilized for development of such products which will have high nutritional value and low cost.